STUDY OF PREVALENCE AND RISK FACTORS OF VIRAL HEPATITIS C AMONG THE ADULT POPULATION IN UZBEKISTAN (International journal of medical sciences, 2026)
A current study of HCV among the adult population of Navoi Region, conducted in 2025, found that the prevalence of infection was approximately 6%. Surgical interventions emerged as the most significant risk factor, highlighting the need for enhanced sterility monitoring and adherence to infection safety standards during medical procedures. The findings highlight the importance of expanding preventive programs, improving educational initiatives for medical personnel and the public, and implementing systematic infection safety monitoring in healthcare facilities across the region.